Dimensions of Water Resources Regulation in Philosophy of Justice and Human Rights Perspective (Journal of Indonesian Legal Studies, 2022)
Management of water resources is closely related to the availability of access to clean water for the community and has direct implications for social justice and the fulfillment of basic human rights. However, various arrangements in the management of water resources in Indonesia are considered not in favor of the concept of justice and are more directed towards commercialization and capitalization. This research is intended to examine, analyze, and criticize laws and regulations related to water resources. By consdiering several multidisciplinary aspects in the laws and regulations in the field of water resources, including aspects of justice and human rights, this research also analyzes from the philosophical, legal, and sociological aspects. This research found and emphasize that the concept of Pancasila can be a legal political basis for the state's right to control water resources to be directed so that the management of water resources does not oppress those who are socially and economically weak, or the poor. The availability of water is constant, while the demand for water is increasing in quantity and quality, then what will happen is scarcity. At this stage of water scarcity, the principle of justice becomes very important in water management. Access to water justice is not individual or micro justice, but social or macro justice. Justice to get water as a human right cannot be left to everyone based on a market mechanism, but government intervention to ensure the fulfillment of the right to water, at least is very much needed.